A concise and practical stereoselective synthesis of ipragliflozin L-proline - Ma, Shuai; Liu, Zhenren; Pan, Jing; Zhang, Shunli; Zhou, Weicheng (Beilstein Journal of Organic Chemistry, 2017)
A concise and practical stereoselective synthesis of ipragliflozin L-proline was presented starting from 2-[(5-iodo-2-fluorophenyl)methyl]-1-benzothiophene and 2,3,4,6-tetra-O-pivaloyl-α-D-glucopyranosyl bromide without catalyst via iodine–lithium–zinc exchange. The overall yield was 52% in three steps and the product purity was excellent. Two key diastereomers were prepared with efficient and direct access to the α-C-arylglucoside.
Keywords: arylzinc derivative; β-C-arylglucoside; diastereomer impurity; ipragliflozin L-proline; stereoselective synthesis